Patient-Centered Outcomes in Surgical and Orthodontic Treatment - Phillips, Ceib (1999)
Patient-centered health care has two characteristics: it is closely congruent with and responsive to the patient's wants, needs, and preferences, and it considers the psychological, social, cultural, and economic dimensions of the patient in addition to physical findings. The ultimate benefit to the patient has always been a primary concern of clinicians providing coordinated orthodontic and orthognathic surgical treatment. However, in the past 10 years, a much greater emphasis has been placed in both medicine and dentistry on the patient as a coparticipant in decision making and the process of treatment. In addition, it has been realized the success of treatment must be defined not just in terms of the objective findings of clinicians, but also in the context of the patient's perceptions of what was achieved. This article discusses the impact of the new emphasis on patient-centered care on clinical practice and research in orthodontics and orthognathic surgery and provides two examples of how patient-centered outcomes can be assessed and used to improve the quality of care in these patients.